2017
DOI: 10.3171/2016.7.jns161263
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of traumatic brain injury with 17α-ethinylestradiol-3-sulfate in a rat model

Abstract: OBJECTIVE17α-ethynylestradiol-3-sulfate (EE-3-SO4) is a highly water-soluble synthetic estrogen that has an extended half-life (∼ 10 hours) over that of naturally occurring estrogen (∼ 10 minutes). In this study, EE-3-SO4 was evaluated in a lateral fluid percussion–induced traumatic brain injury (TBI) model in rats.METHODSA total of 9 groups of Sprague-Dawley rats underwent craniectomy. Twenty-four hours later, lateral fluid percussion was applied to 6 groups of animals to induce TBI; the remaining 3 groups se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 51 publications
1
23
0
1
Order By: Relevance
“…Similarly, we found no major effect of lateral FPI on performance in the open-field test. Previously, Kim et al 39 and Fucich et al 40 assessed rats with lateral FPI at D4 and D7 postinjury, respectively, and found that the injured rats spent less time than controls exploring the center of the open field. Similarly, Schultz et al 14 reported that rats with severe lateral FPI spent slightly less time than sham-operated controls in the inner arena at 1 and 3 months, but not at 6 months post-TBI; however, there was no difference between the epileptic and nonepileptic animals.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we found no major effect of lateral FPI on performance in the open-field test. Previously, Kim et al 39 and Fucich et al 40 assessed rats with lateral FPI at D4 and D7 postinjury, respectively, and found that the injured rats spent less time than controls exploring the center of the open field. Similarly, Schultz et al 14 reported that rats with severe lateral FPI spent slightly less time than sham-operated controls in the inner arena at 1 and 3 months, but not at 6 months post-TBI; however, there was no difference between the epileptic and nonepileptic animals.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that administration of estrogen 1 hour following traumatic brain injury produces various beneficial effects, such as markedly reduced cerebral edema, decreased neuronal degeneration and improvement of memory and cognitive functions [ 57 59 ]. Furthermore, studies have shown that estrogen administration following spinal cord injury also produces salutary effects [ 60 , 61 ].…”
Section: Gender Dimorphism In Trauma Shock and Sepsismentioning
confidence: 99%
“…Finally, DTI-MRI has been used as read-out of treatment efficacy in rodents' models of TBI. In particular, DTI has revealed the beneficial effect on white matter integrity of activation of mitochondrial calcium fluxes (Parent et al, 2020 ), of autophagy modulators (Medina et al, 2017 ; Yin et al, 2018 ), estrogens (Kim et al, 2015 , 2017 ), metamphetamine (Ding et al, 2013 ), erythropoietin (Robinson et al, 2016 , 2018 ), tissue plasminogen activator (in mice; Xia et al, 2018 ), mGluR5 (in mice; Byrnes et al, 2012 ), and dietary modulations (Shultz et al, 2015 ; Schober et al, 2016 ; Tan et al, 2016 ). Notably, the detrimental effect of alcohol in TBI was also investigated by DTI (Kong et al, 2013 ).…”
Section: Applications To Models Of Neurodegenerative Diseasesmentioning
confidence: 99%